The Impact of Azerbaijan’s National Economic Development on Tourism Sector - Hajiyev, Natig Gadim?Oglu; Humbatova, Sugra Ingilab; Abidi, Solmaz Aghazaki (Journal of Eastern European and Central Asian Research (JEECAR), 2022)
This article the influence of GDP on travel vouchers in a long- and short-term perspective, travel vouchers sold to Azerbaijani citizens for long-term internal journeys, the price of travel vouchers sold to Azerbaijani citizens, the number of beds per person in a day, the number of beds per all citizens in a day, and the number of residential areas per citizens. In addition, it analyzes the impact of GNI on those same items. Unlike other research about the influence of tourism development on GDP, this article examines the reverse impact - the impact of GDP on tourism development. In Azerbaijan, the primary source of GDP growth is the export of energy resources. Tourism is not major contributor to economic development. The problem, therefore, is to find alternative ways to develop tourism based on the economic growth that comes from the export of energy resources. To explain this further, tourism development should rely on supply rather than the demand generated by GDP and GNI growth. As a result, GDP positively affects tourism development while GNI has a negative impact. We recommend considering the development of a stable supply for tourism that is not dependent on the revenues derived by energy exports.